Fine-scale characteristics of the 7-8 May 1995 squall line as revealed by ELDORA - Kankiewicz, J. Adam, author (Colorado State University. Libraries, 1998)
During the VORTEX-95 campaign, the Electra Doppler Radar (ELDORA) passed through the transition zone of a maturing squall line that formed over the Southern Plains late on 7 May 1995. A leading line of convection, a transition zone, and a developing trailing stratiform region of precipitation composed the precipitation structure of this squall line. Descending rear-to-front flow and ascending front-to-rear flow predominated in the line perpendicular flow. In the line-parallel direction, there was strong southerly along-line flow advecting hydrometeors to the north end of the line. An along-line average of reduced-resolution data revealed a rearward tilted updraft within the convective line, behind which lay a secondary band containing a mesoscale updraft/downdraft couplet. The fine-scale observations made by ELDORA have provided new insight into the inner structure of maturing linear squall lines. Horizontal flow was highly variable within the convective line, with strong evidence of acceleration of the mean flow (e.g., Bernoulli flow) around updraft cores. Flow rearward of the convective line was much less perturbed. Within the stratiform region, an along-line jet was observed near the 0°C level, possibly arising from a melting-induced stable layer. In contrast to the coarse-resolution analysis, high-resolution data showed updrafts within the convective line to be erect with peak updraft velocities centered at increasing elevations behind the leading edge of the line. Also, these data showed the stratiform region to be comprised of many small-scale updrafts and downdrafts at all levels. Thus, the appearance of a tilted updraft signature in the convective line and a broad mesoscale updraft/downdraft couplet through the stratiform region arises from spatial filtering. Further analysis of the vertical velocity field within this squall line revealed evidence for high-frequency gravity wave oscillations. General characteristics of these thermally-forced gravity waves included wavelengths of 5-10 km and amplitudes of 2-5 m s-1. Additional evidence for these gravity waves came by the observed quadrature relationship between the vertical motion field and perturbations in the line-perpendicular flow. Though hinted at in previous studies, this study offers the first observational confirmation of gravity wave existence within the stratiform region of a squall line as predicted by recent two-dimensional modeling studies. The three-dimensional behavior of these waves is consistent with recent modeling studies of elevated heat sources in a sheared environment. Contoured Frequency by Altitude Diagram (CFAD) analyses of the kinematic and precipitation fields confirmed this squall line was in the early stages of its existence. Additionally, mass-weighted CFADs confirmed that upward mass transport was dominated by moderate to strong updrafts (in contrast to recent draft statistics presented for Florida convection). Substantial mid-level downward mass transport was also noted, indicating that significant subsidence occurred close to the leading line of convection.
Summer 1998.
Keywords: Squall lines; Convection (Meteorology)